EFFECT OF INORGANIC ZINC FERTILIZATION ON GROWTH AND YIELD OF FENUGREEK (Trigonella foenum-graecum L.) - Fatih Hasen (Mesopotamia Journal of Agriculture)
A pots experiment was carried out under plastic house conditions to study the effects of six zinc treatments(0ppm، 5ppm ,10ppm، 0ppm+foliar 50mg zn.L-1، 5ppm +foliar 50mg zn.L-1 and 10 ppm + foliar 50mg zn.L-1) on vegetative growth, yield and zinc concentration in seed of fenugreek planted in clay and silty clay soils.The treatment o، 5، 10 ppm added to soil before sowing and foliar applied after two months of sowing. Zinc added as ZnSO4.7H2O.. The results showed that addition of zinc caused a significant increase on most vegetative growth characters (dry matter, plant height، number of tiller and leaves)، yield constituents characters (number and weight of pods, grain yield) and also increase zinc concentration in seeds in the both soils. Treatment of 10 ppm Zn and foliar application with 50 mg Zn.liter-1 (F+Zn3) gave highest values among all treatments on characters studied.The studied soils differed in their response to zinc fertilization.